1986
DOI: 10.1007/bf00174366
|View full text |Cite
|
Sign up to set email alerts
|

Lithium and bupropion antagonise the phasic changes in locomotor activity caused by dopamine infused into the rat nucleus accumbens

Abstract: Dopamine infused persistently (25 micrograms/24 h for 13 days) into the nucleus accumbens of rat brain caused phasic increases in spontaneous locomotor activity during the period of infusion. This phasic responding was prevented by lithium administered throughout the infusion period in divided doses (3 X daily administrations of 2.5 mg/kg IP) or as a continuous IP infusion (7.5 mg/kg/24 h), and by bupropion treatment (5-20 mg/kg 3 X daily). In contrast, imipramine, amitriptyline and nomifensine failed to preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…For instance, as early as in 1971, behavioral observations in rodents have shown that lithium, which is now known to inhibit GSK3, can antagonize locomotor activity induced by drugs elevating dopaminergic tone or by the direct injection of dopamine in the nucleus accumbens (Cox et al, 1971; Barnes et al, 1986; Aylmer et al, 1987). However, these studies were all conducted before the discovery of the effect of lithium on GSK3 (Klein and Melton, 1996; Stambolic et al, 1996), and the actions of lithium in these experimental systems were generally attributed to other mechanisms including changes in dopamine release or dopamine receptor blockade.…”
Section: The Regulation Of Akt and Gsk3 By D2 Dopamine Receptorsmentioning
confidence: 99%
“…For instance, as early as in 1971, behavioral observations in rodents have shown that lithium, which is now known to inhibit GSK3, can antagonize locomotor activity induced by drugs elevating dopaminergic tone or by the direct injection of dopamine in the nucleus accumbens (Cox et al, 1971; Barnes et al, 1986; Aylmer et al, 1987). However, these studies were all conducted before the discovery of the effect of lithium on GSK3 (Klein and Melton, 1996; Stambolic et al, 1996), and the actions of lithium in these experimental systems were generally attributed to other mechanisms including changes in dopamine release or dopamine receptor blockade.…”
Section: The Regulation Of Akt and Gsk3 By D2 Dopamine Receptorsmentioning
confidence: 99%
“…However, the signaling mechanisms mediating the action of DA on hyperactivity are still not fully understood. For instance, acute administration of lithium salts is known to antagonize the hyperactivity induced by various dopaminergic agonists (8)(9)(10)(11). Nevertheless, the mechanism by which lithium interferes with DA-associated behavior remains uncharacterized.…”
mentioning
confidence: 99%
“…It is conceivable, therefore, that any effects of lithium and valproate could be due to direct attenuation of the effects following release of these neurotransmitters, particularly dopamine. Certainly there is some support for suggestions that dopamine-induced changes can be attenuated by chronic treatment with lithium in animal studies (Cox et al, 1971;Flemenbaum, 1977;Barnes et al, 1986), although not in all studies (Cappeliez and Moore, 1990), and may also inhibit amphetamine-induced behaviors (Lerer et al, 1984). There is also some evidence that in animals chronic lithium may reduce dopamine release in response to amphetamine or cocaine (Berggren, 1985;Gambarana et al, 1999).…”
Section: Discussionmentioning
confidence: 88%